Program Edukasi Sekolah “UNIBANG Goes to School” - Timbul Pardede; Fikri Ramadhan; Deliza Halimatusadiah (Universitas Bhakti Asih Tangerang, 2026)
School education program “the UNIBANG Goes to School” is a community development initiative aimed at improving the quality of human resources in school environments through educational, participatory, and sustainable approaches. This program is designed as a contribution of higher education institutions in addressing educational challenges, particularly in enhancing academic literacy, 21st-century skills, and students’ awareness of career planning and self-potential development. The program targets secondary school students, teachers, and school management as strategic partners in its implementation. The implementation methods include integrated activities such as socialization, training, mentoring, and evaluation organized around several main themes, namely strengthening learning motivation, developing communication skills, introducing digital technology, and providing basic understanding of higher education. Activities are conducted through interactive workshops, simulations, group discussions, and hands-on practice that emphasize contextual learning. In addition, this program encourages active student participation to help them identify their potential, build self-confidence, and formulate realistic educational goals. The expected outcomes of this program include increased student awareness of the importance of continuing education, the development of positive attitudes toward the learning process, and the establishment of sustainable partnerships between Universitas Bhakti Asih (UNIBANG) and partner schools. This program is expected to serve as an adaptive, education-based community development model oriented toward youth empowerment and for the sustainability program